Global research trends in food safety in agriculture and industry from 1991 to 2018: A data-driven analysis. (March 2019) - Hu, Kai; Liu, Juan; Li, Bin; Liu, Lili; Gharibzahedi, Seyed Mohammad Taghi; Su, Ye; Jiang, Yongnian; Tan, Jinglu; Wang, Yingkuan; Guo, Ya
Abstract: Food safety (FS), as a topic important to human health and wellbeing, has attracted a great deal of attention. With the large volume of publications in the area, it is hard to gain a comprehensive picture of the research trends. A scientometric data-driven analysis of the field can help reveal the diverse facets of FS. Food safety is critical in two important stages of the food system: food production and food processing, which are categorized as agriculture food safety (Agric-FS) and industry food safety (Ind-FS), respectively. In this work, these two closely-related but different research fields are comparatively analyzed. Based on scientometric theory and metrics, characteristics of both fields are discussed in terms of annual research output, active journals, important authors, and countries of activities. The overall output of publications is in an upward trend and the dynamics of publications in the two areas are in a similar pattern. Food Control and Journal of Food Protection are both representative journals for Agric-FS and Ind-FS. Jacxsens L, Uyttendaele M, LeJeune J, and Luning P are representative authors for Agric-FS and Jacxsens L, Griffith CJ, Luning P, and Uyttendaele M are representative authors for Ind-FS. The USA is the leading country in both fields by volume of output, followed by the UK and China. The research focus areas over time are extracted by temporal co-word and co-citation analysis. It was found that the Agric-FS domain is more unevenly distributed. Early studies in Agric-FS topics have divergent directions because of divergent fresh produce. Important topics in later times are focused on foodborne disease and supply chains that support the fresh produce. In contrast, the Ind-FS focus has more focal topics, and the research is concentrated on theories, tools, and practical issues in food quality and safety. Control methods such as HACCP are the focuses of early research in Ind-FS. More practical issues concerning barriers for quality controls are studied in later periods, including human-related problems in business activities. Highlights: Agriculture related and Industry related Food Safety were summarized and compared. Local and global citation scores were used to analyze the scientific activities. Co-word and Co-citation networks were built to find meaningful structures. Several interesting observations are provided.